2003
DOI: 10.1097/00003226-200303000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Corneal Stroma in Rabbits After Intrastromal Corneal Ring Implantation

Abstract: Tissue response to these corneal inserts includes keratocyte activation, intracellular lipid accumulation, and new collagen formation. Our histologic findings suggest that these deposit formations are not lipofuscin accumulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 15 publications
3
45
0
1
Order By: Relevance
“…Histologically, several findings underline the biocompatibility of both groups, since there was no evidence of an inflammatory response at 30 and 90 days. All the samples showed hypoplasia of the epithelium over the segments and an increased keratocyte density at the edges of the rings, these findings being in agreement with previous works [14,15]. Several studies reported that the deposits observed on biomicroscopic examination consist of intracellular lipid accumulations and new collagen formation.…”
Section: Groups/ Treatmentsupporting
confidence: 91%
See 4 more Smart Citations
“…Histologically, several findings underline the biocompatibility of both groups, since there was no evidence of an inflammatory response at 30 and 90 days. All the samples showed hypoplasia of the epithelium over the segments and an increased keratocyte density at the edges of the rings, these findings being in agreement with previous works [14,15]. Several studies reported that the deposits observed on biomicroscopic examination consist of intracellular lipid accumulations and new collagen formation.…”
Section: Groups/ Treatmentsupporting
confidence: 91%
“…Several studies reported that the deposits observed on biomicroscopic examination consist of intracellular lipid accumulations and new collagen formation. These deposits were observed in the edges of the segment where increased cell density was present, being a connection between the deposits and the keratocyte activation stimulated by the wound-healing response [14]. The presence of myofibroblast in this zone suggested an active wound-healing process.…”
Section: Groups/ Treatmentmentioning
confidence: 85%
See 3 more Smart Citations